Identifying stakeholders and collaborating with communities - Best, Marina; Irvine, Robyn; Bako, Longji; Citegetse, Geoffroy; Field, Alison; Roe, Dilys; Rose, David Christian; Spencer, Jonathan (OpenBook Publishers, 2022)
Working with communities, including local and Indigenous communities, is fundamental to most successful conservation practice. Key elements include determining the appropriate level of engagement, identifying the key stakeholders, identifying appropriate means of collaborating with different stakeholders, creating and maintaining trust, and collaborating to deliver the objectives.